A Review On Carbon Nanotubes Production Via Catalytic Methane Decomposition. - Chai, S.P.; Zein, S.H.S.; Mohamed, A.R. (2004)
Methane decomposition is a promising approach to produce high purity, high yield and perfect orientation of carbon nanotubes and is viable for scaling up its production at a relatively low cost.